A constituição da educação infantil no município de Aracruz-ES : permanências e descontinuidades - Lomba, Maria Lúcia de Resende (2013)
This work investigates the process of creating the kindergarten "Epifânio Pontin". We seek to understand the formation of early childhood education in the municipality of Aracruz, Espírito Santo State, Brazil. We search the configuration of curriculum guidelines and pedagogical practices that permeated the creation of the first municipal kindergarten and its transition to the Municipal Center for Early Childhood Education (CMEI) in the period 1969-2009. The documental corpus is based on: pedagogical proposals of the city and CMEI; evaluation forms for children; records from the municipal institutions of childhood education; CMEI minutes of meetings; agendas of class teachers; videos; a teacher's notebook with her notes; graduation invitation; photographs; agendas studies; a correspondence; clippings from local newspapers; a questionnaire and interviews. Based this work on the propositions of Bloch (2001) and Ginzburg (1989, 2002, 2006, 2007), we establish approximations to the historical research in the process of analysis of documentation and relationships between the past and the present. In order to points of conflict, tensions, and power relations that permeate the production of the sources, those are understood as clues, traces, marks, and signs to be read in its complexity. This work dialogues with Simões (2006, 2011) and Faria Filho (1998) on the importance of studying the past to understand the journey of teaching in the Brazilian scene. We base on Kuhlmann Jr. (1998, 2000, 2001, 2005, 2010); Del Priori (2010), Kramer (1994, 1995, 2003, 2006, 2011), Hoffmann (2006) and Silva (2007, 2008) to think about issues related to Early Childhood Education, regarding: the history; policies and conceptions which influenced the proposals developed in Brazilian institutions; challenges relating to the construction of knowledge; continued training of teachers; assessment of children and waiting lists for vacancies in institutions. We considers that the process is permeated by continuities and discontinuities. In regard to continuities, we find the extensive waiting list for vacancies in municipal institutions, as well as insecurity, inadequacy and improvisation of physical spaces allocated to this first stage of basic education. The discontinuities refer to the intensification of the processes of continuous formation of teachers; attempts to break with pedagogical activities guided by holidays and themes; the evaluation process of children; and the pursuit of building a new pedagogical proposal for the municipal Childhood Education